2019
DOI: 10.1590/1678-4499.20180408
|View full text |Cite
|
Sign up to set email alerts
|

Selecting “the best” nonstationary Generalized Extreme Value (GEV) distribution: on the influence of different numbers of GEV-models

Abstract: The selection of an appropriate nonstationary Generalized Extreme Value (GEV) distribution is frequently based on methods, such as Akaike information criterion (AIC), second-order Akaike information criterion (AICc), Bayesian information criterion (BIC) and likelihood ratio test (LRT). Since these methods compare all GEV-models considered within a selection process, the hypothesis that the number of candidate GEV-models considered in such process affects its own outcome has been proposed. Thus, this study eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
(94 reference statements)
1
6
0
Order By: Relevance
“…The results found in this simulation round indicate that the BIC also tends to perform poorly when the dispersion of the series increases over time. This statement is consistent with results found by Xavier et al (2019b).…”
Section: Third Simulation Round: Synthetic Series Generated From Nons...supporting
confidence: 94%
See 2 more Smart Citations
“…The results found in this simulation round indicate that the BIC also tends to perform poorly when the dispersion of the series increases over time. This statement is consistent with results found by Xavier et al (2019b).…”
Section: Third Simulation Round: Synthetic Series Generated From Nons...supporting
confidence: 94%
“…For the highest values of the sample size, μ 0 and σ 0 , the ΔAICc tended to outperform all other methods. The tendency of both AIC and AICc to select more complex models (Panagoulia et al, 2014;Kim et al, 2017;Xavier et al, 2019b) was also observed. These two criteria selected the most complex model (Model 3) at rates considerably higher than the other procedures.…”
Section: Second Simulation Round: Synthetic Series Generated From Non...mentioning
confidence: 81%
See 1 more Smart Citation
“…Regarding simulation studies involving distributions of extreme values, Xavier et al [48] have reported in their simulation studies involving the generalized extreme values distribution, in the presence of covariates to model trend or temporal effect. The one that is more parsimonious is preferable and that according to the subject of study, the method used to select models is an important issue.…”
Section: Simulation Study To Evaluate Goodness Of Fit For Extreme Valmentioning
confidence: 99%
“…From an agrometeorological perspective, this selection process is expected to describe if and how the probability of the Tmax and Tmin events have changed over the last 133 years in Campinas-SP and if these changes are significantly correlated with the global air temperature. As pointed out by authors such as Cannon (2010); Coles (2001);El Adlouni et al (2007) and Xavier et al (2019a), this selection process should be based on the principle of parsimony, which seeks to choose the most parsimonious candidate model. In other words, this principle attempts to select the simplest model that explains as much of the variation in the data as possible (Coles 2001).…”
mentioning
confidence: 99%